Penerapan model cooperative learning tipe STAD untuk meningkatkan kemampuan pemahaman konsep matematika siswa sekolah dasar - Dinda Nurul Aulia; Asep Samsudin; Ilham Kurniawan (Journal of Didactic Mathematics, 2023)
This study aims to learn about the application of the Cooperative Learning Model Type STAD and the improvement of the ability to understand the mathematical concepts of mixed counting operations in students of SDN Cilame Grade 3. Cooperative Learning Type Model STAD is a learning technique that can be used to invite students to discuss, help each other, and cooperate in solving tasks. Their learning is divided into small groups. The research used is qualitative. The subject of research is students of SDN Cilame Class III, out of a total of 25. The instrument used in the research is the test drawing prepared by the researcher. The data analysis techniques used are descriptive qualitative techniques to obtain data by collecting student test results and comparing improvement results with circumstances and before. This study was conducted in three meetings to see whether the application was increased or not at all. Based on the results of research and discussion on this study, it can be concluded that there is an excellent improvement in the understanding of mathematical concepts in students. We obtained a good response from students and teachers on the application of learning models and found that the difficulties experienced by students are related to indicators that show an understanding of the mathematics concepts.